An extensible framework for collaborative e-governance platform workflow modeling using data flow analysis. Issue 3 (3rd July 2017) - Liu, Luning; Ju, Jingrui; Feng, Yuqiang
ABSTRACT: As IT-enabled collaborative technologies facilitate the transformation from government to governance, governments are working to establish collaborative e-governance platforms across organizational boundaries in different contexts, especially in developed countries. In contrast, most developing countries are still at a nascent stage of platform construction. There is little research investigating the function-oriented across-organization platform modeling required to drive platform design and development for developing countries. Therefore, we propose a framework for collaborative e-governance platform workflow modeling, including three level-extensible dimensions of requirement, method, and model. Specifically, we identify four basic functions and eight patterns, extend a method of object-oriented workflow modeling using data flow analysis, and separately model the platform on the top level and object level. Finally, we apply the framework to a citizen appeal processing platform to validate its utility. The framework provides an operable method and reusable function object models, which contribute to the contextualized collaborative e-governance platform modeling for developing regions.